A Close Look at Lyα Emitters with JWST/NIRCam at z ≈ 3.1 - Liu, Yixiao; Dai, Y. Sophia; Wuyts, Stijn; Huang, Jia-Sheng; Jiang, Linhua (The Astrophysical journal, 2024)
We study 10 spectroscopically confirmed Ly α emitters (LAEs) at z ≈ 3.1 in the Ultra Deep Survey field, covered by the James Webb Space Telescope/NIRCam in the Public Release Imaging for Extragalactic Research program. All LAEs are detected in all NIRCam bands from F090W to F444W, corresponding to rest frame wavelengths of 2200 Å to 1.2 μ m. Based on morphological analysis of the F200W images, three out of the 10 targets are resolved into pair-like systems with separations of <0.″9, and another three show asymmetric structures. We then construct the spectral energy distributions (SEDs) of these LAEs, which show little to no extinction. All sources, including the pairs, show similar SED shapes, with a prominent flux excess in the F200W band, corresponding to extremely strong [O iii ]+H β emission lines (EW rest = 740–6500 Å). The median effective radii, stellar mass, and UV slope of our sample are 0.36 kpc, 3.8 × 10 7 M ⊙ , and −2.48, respectively. The average burst age, estimated by stellar mass over star formation rate, is <40 Myr. These measurements reveal an intriguing starbursting dwarf galaxy population lying off the extrapolations of the z ∼ 3 scaling relations to the low-mass end: ∼0.7 dex above the star-forming main sequence, ∼0.35 dex below the mass–size relation, and bluer in the UV slope than typical high- z galaxies at similar UV luminosities. We speculate that these numbers may require a larger main-sequence scatter or tail in the dwarf galaxy regime toward the starburst outliers.